Critical Success Factors of Implementation of Fishing License at the Ministry of Marine Affairs and Fisheries - Muhammad Reza Budiman; Rita Myrna; Mas Dadang Enjat Munajat (AMAR (Andalas Management Review), 2022)
Business Licensing for the Capture Fisheries Sub-sector is a capture fisheries business license policy for business actors that are carried out electronically. The purpose of this study was to analyze critical success factors (CSFs) for the implementation of capture fisheries business licensing at the Ministry of Maritime Affairs and Fisheries. This research is quantitative with the data collection method using a questionnaire. Respondents are executors of business licensing for capture fisheries at the KKP. Data analysis used Structural Equation Modeling (SEM) with SmartPLS 4.0 tools. The research results obtained stated that the implementation of the policy was influenced by the variable’s quick, clear, and two-way communication and the correct location of implementation. On the other hand, four other variables, including sufficient and effective use of budget, correct organizational structure, involvement of people, and adequate equipment and appropriate technology, are concluded to not affect on the performance of implementing business licensing in the capture fisheries sub-sector.